(untitled) (Revista Electrónica REDINE, 2018)
This qualitative research general objective was uncovering the meanings and senses that pay primary school teachers to recreation in the orientation of the behavior of adolescents. The study was addressed from the paradigm of interpretive, using the ethnographic method. On the other hand, the stakeholders of the study were five teachers of primary education in the educational unit "Vicente Salias", located in the municipality of Iribarren, parish Cathedral of Barquisimeto, Lara state. For its part, the corpus of information was collected by means of techniques of interview and participant observation in depth, being interpreted by the process of coding and categorizing suggested by the model Glater. The categories that emerged were committed teaching strategies for transformation, regulating empathy and reformulation of judgments about itself. Among them finds more significant is revealed that for them teachers, the recreation represents a strategy that enables the compliance of their roles as guiding, its use is linked with them beliefs that have on the duty be of the teaching. In that order of ideas, for them actors social cobra sense it recreation, since starting from she, can promote the training integral of them adolescents, modifying the behavior aggressive through the progressive consolidation of skills personal and social that you contribute to establish an interaction respectful and empathic.